Finance and crisis: Marxian, institutionalist and circuitist approaches - Georgios Argitis; Trevor Evans; Jo Michell; Jan Toporowski (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2014)
Most mainstream neoclassical economists completely failed to anticipate the crisis which broke in 2007 and 2008. There is however a long tradition of economic analysis which emphasises how growth in a capitalist economy leads to an accumulation of tensions and results in periodic crises. This paper first reviews the work of Karl Marx who was one of the first writers to incorporate an analysis of periodic crisis in his analysis of capitalist accumulation. The paper then considers the approach of various subsequent Marxian writers, most of whom locate periodic cyclical crises within the framework of longer-term phases of capitalist development, the most recent of which is generally seen as having begun in the 1980s. The paper also looks at the analyses of Thorstein Veblen and Wesley Claire Mitchell, two US institutionalist economists who stressed the role of finance and its contribution to generating periodic crises, and the Italian Circuitist writers who stress the problematic challenge of ensuring that bank advances to productive enterprises can successfully be repaid.
Keywords: B14; B15; B24; B25; E11; E32; 330; capitalism; finance; crisis